Cacao (Theobroma cacao L.) Resistance Evaluation Againts Black Pod Diseaseand Effectiveness of Inoculation Methods - Rubiyo Rubiyo; Agus Purwantara; Dedy Suhendy; Trikoesoemaningtyas Trikoesoemaningtyas; Satriyas Ilyas; Sudarsono Sudarsono (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2008)
The general objective of this experiment was to standardize method of resistance evaluation of cacao germplasm against Phytophthora palmivora, the pathogen causing black pod disease in cacao. The sepecific objectives were to evaluate (1) effects of inoculum type and pod injury, (2) effects of inoculum type and seedling injury, and (3) effects of genetic background of cacao seedlings on infection of P. palmivora. In this experiment, effectiveness of either zoospora or mycellia was evaluated as inoculation sources for pod, leaf and stem of cacao clone GC 7 and Sca 12. Part of the tested cacao pods, leaves, and stems were injured prior to P. palmivora inoculation while the others were not. Observations were conducted on diameter of the necrosed symptoms on inoculated cacao pods, number of necrosed spot on inoculated leaf, and the length of necrosed symptoms on stem of tested cacao seedlings. Results of the experiment indicated inoculation using mycelia of P. palmivora was more effective than zoospora and injuring the tested cacao pods and seedlings before P. palmivora inoculation can be used to prediction the resistance of tested cacao clones against P. Palmivora infection. Results of resistance prediction using detached pod assay was similar to that of using seedling assay; therefore, seedling assay could be used as an alternattive method of resistance evaluation. Cacao F1 hybrids derived from TSH 858 x Sca 12 showed some resistance against P. palmivora and they might potentially result in high yielding lines.Key words: Phytophthora palmivora, cacao breeding, germplasm evaluation, inoculation standardization, pod assay, seedling assay.